2018
DOI: 10.1097/htr.0000000000000292
|View full text |Cite
|
Sign up to set email alerts
|

IMPACT Score for Traumatic Brain Injury: Validation of the Prognostic Tool in a Spanish Cohort

Abstract: The IMPACT model validates prediction of 6-month outcomes in a Spanish population of moderate-severe TBI. IMPACT Lab model is the one that presents a higher discriminative capacity. These results encourage the implementation of the IMPACT model as a prognostic tool in the management of patients with TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
5
5
0
Order By: Relevance
“…The maximum age of the patients was 81 years with median age of 33 years. This result is consistent with the study done by Egea-Guerrero et al 11 which showed median age of 41 years. Panczykowski et al 12 and Olivecrona et al 13 did their study on adult patients with severe TBI who had mean ages of 37.8 and 35.5 years respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The maximum age of the patients was 81 years with median age of 33 years. This result is consistent with the study done by Egea-Guerrero et al 11 which showed median age of 41 years. Panczykowski et al 12 and Olivecrona et al 13 did their study on adult patients with severe TBI who had mean ages of 37.8 and 35.5 years respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the overall unfavorable outcome and mortality observed in our study was 28.8% and 17.3% respectively. This is consistent with the study done by Egea-Guerrero et al 11 which showed unfavorable outcome and mortality as 25.5% and 16.2% respectively in patients with moderate to severe TBI. In a study done by Panczykowski et al 12 in a cohort of severe TBI patients, 73% had unfavorable outcome and 41% had mortality in 6 months.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Different studies have been conducted into the validation of these models. In these studies, patients with severe and moderate traumatic brain injury have been evaluated, and use of the different models and scores has shown that their performance and sensitivity is high [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to evaluating the association between sleep apnea and occurrence of brain injuries, we evaluated the association between sleep apnea and severities of brain injuries. Information regarding Glasgow Coma Scale or IMPACT score (20) was unavailable in the NHIRD. Therefore, we used intensive care unit (ICU) use and mortality following a brain injury episode as our research outcomes.…”
Section: Outcome and Relevant Variablesmentioning
confidence: 99%